Relationship of Remote Work Arrangements and Productivity of Accountants in a Philippine-Based Global Accounting Firm - Luz E. Celestino; Gianne Carla B. Angana; Gloria D. Calado; Seth R. Cervantes; Evangeline M. De Vera; Karl LJ D. Frias; Jesus P. Briones (Research Synergy Foundation, 2025)
Work set-up plays a crucial role in determining employee productivity. This study assessed the relationship between remote work arrangements and productivity of accountants in a Philippine-based global accounting firm. Utilizing a descriptive-correlational methodology, data were collected through a researcher-structured questionnaire administered virtually to 60 randomly sampled accountants. Statistical tests including frequency, percentage, weighted mean, and Pearson correlation coefficients (r) were employed in the data analysis. The findings revealed that remote work arrangements enhanced accountants’ flexibility, work-life balance, employee well-being, and team communication, indicating that the firm’s remote work policies are effectively implemented and are aligned with employees’ needs. Furthermore, the study revealed that respondents can efficiently work, provide good quality output, and consistently meet deadlines, showing enhanced productivity. Consequently, findings showed a highly significant and positive relationship between all dimensions of remote work arrangements and productivity suggesting that offering flexibility and allowing employees to self-regulate and structure tasks independently results in efficient, accurate, and consistent output. Moreover, results revealed that problems including blurred work-life boundaries, isolation, miscommunication, and technological barriers are experienced when on remote work set-up. Theoretically, the study reinforces Self-Efficacy Theory, affirming that accountants’ productivity is influenced by the belief to successfully perform tasks remotely. Finally, the researchers proposed strategies to further enhance productivity during remote work set-up. This study can be used by corporate leaders to enhance internal policies on remote work arrangements, ensuring that policies support enhanced productivity.